Case Report: Efficacy of albumin dialysis for the reversal of bile cast nephropathy-induced acute kidney injury - Issac, Aaron G.; Yu, Michael A.; Rogers, Desiree M.; Subramanian, Ram M. (Frontiers in Nephrology, 2023)
Background: Bile Cast Nephropathy (BCN) is an underdiagnosed renal complication associated with severe hyperbilirubinemia and seen in patients with liver failure who have cholestatic complications. BCN induced acute kidney injury (AKI) can require hemodialysis (HD), and Molecular Adsorbent Recirculating System (MARS) is a potentially useful therapeutic modality. Case Summary: A 57-year-old male presented with one month of jaundice, with labs significant for hyperbilirubinemia and acute kidney injury. Abdominal imaging and biopsy confirmed biliary ductal dilatation secondary to a pancreatic head mass. The patient had rapidly progressive renal failure and refractory hyperbilirubinemia despite biliary decompression, and was started on HD. Subsequent therapy with albumin dialysis therapy using the Molecular Adsorbent Recirculating System (MARS) was successful in reversing the AKI, cessation of HD, and restoration of native renal function.In the setting of bile cast nephropathy induced AKI, timely initiation of Molecular Adsorbent Recirculating System (MARS) can provide a useful therapeutic strategy to reverse renal dysfunction and facilitate intrinsic renal recovery.